Preparation and Evaluation of Intravaginal Ring Containing Drospirenone - Ying Zhang; Chun-Xiao Li; Mei-Ying Ning; Xue-Yan Duan; Ying Liu (Advances in Pharmacological Sciences)
In the present study, we investigated the feasibility of the vaginal administration of drospirenone silicone IVR. The in vitro release characteristics of matrix-type and reservoir-type IVR were compared under sink conditions in 21 days. At the same time, API excipients compatibility and preformulation study was performed by HPLC, IR, and DSC methods. Biocompatibility of reservoir system was evaluated by tolerability on tissue level in rats. It was found that, under strong light exposure, high temperature, and high humidity conditions, drospirenone and excipients had no significant interactions. The daily release of reservoir-type IVR was about 0.5 mg/d sustaining 21 days, which significantly decreased the burst effect compared with the matrix system. When drospirenone was modified by the PVPk30 in the reservoir system formulation, the daily release rate increased to 1.0 mg/d sustaining 21 days. The cumulative release of reservoir-type IVR was fitted to zero release equation. In addition, biocompatibility of drospirenone IVR system in this dosage is safe. It is feasibility feasibile to further developed for safe, convenient, and effective contraceptive drug delivery with reduced dosing interval.